Assessment of the Applicability of Green Building Rating System in Mitigating Impacts of Building Projects - Wahab, Akeem Bolaji; Olaoye, Fola Oluwatimilehin; Omojola, Samuel Oludare; Ngwoke, Nwora Valentine; Ipadeola, Peter Oluwapelumi; Olukoya, Bidemi Funmilola Olukoya (Urban Planning and Construction, 2026)
The study examined Green Building Rating System (GBRS) in use for building projects in Lagos State, Nigeria. The data for the study were collected from primary and secondary sources on the strengths and weaknesses, criteria of assessment, and the required criteria for enhancing their applicability to the Nigerian local context from the identified twelve (12) certified green building projects. Out of eighteen (18) green building experts identified in the study area, thirteen (13) participated in the study. The data obtained were analysed using thematic analysis, priority ranking and fraction method. The results showed that the most prevalent GBRS in use in the study area were Excellence in Design for Greater Efficiencies (EDGE) and Leadership in Energy and Environmental Design (LEED). Limitation in the adoption of the EDGE and LEED was their lack of functionality in the social aspects of sustainability in buildings. The study developed a weighting framework and flowchart representation of the criteria to be considered by the green building experts to enhance applicability of the rating systems. The study concluded that the EDGE and LEED adopted in the study area focused exclusively on the environmental aspects of sustainability that would mitigate impacts of buildings but they should be adapted to include social and economic aspects of sustainability so as to improve their usage in assessing and certifying buildings while the Nigerian government should equally make efforts to develop her own home-grown green building rating system so as to deepen applicability of GBRS in the country.